2010
DOI: 10.1097/aln.0b013e3181d692c2
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Memory Formation during Routine Anesthesia in Children

Abstract: No implicit memory formation during routine anesthesia was demonstrated in children. It is increasingly likely that the potential clinical implications of implicit memory formation are less of a concern for pediatric anesthetists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…The lack of strong evidence for implicit memory formation during anesthesia in children in this study is consistent with other studies of priming during pediatric anesthesia, none of which have found any evidence for this phenomenon . In contrast to previous studies that found no evidence whatsoever for implicit memory formation, this study found borderline evidence in one of the lists.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The lack of strong evidence for implicit memory formation during anesthesia in children in this study is consistent with other studies of priming during pediatric anesthesia, none of which have found any evidence for this phenomenon . In contrast to previous studies that found no evidence whatsoever for implicit memory formation, this study found borderline evidence in one of the lists.…”
Section: Discussionsupporting
confidence: 83%
“…Several previous studies have failed to find any evidence for implicit memory formation during pediatric anesthesia. This may be because children simply do not form implicit memories during anesthesia or due to the methodological limitations inherent in implicit memory detection during anesthesia in children.…”
Section: Introductionmentioning
confidence: 82%
“…I N a study published this month, the authors played a sound during anesthesia and then determined afterward whether patients preferentially remembered that sound. 1 When one considers learning during anesthesia or sleep, what first comes to mind is that the learner is awake. Assuming that is not the case, as we shall see, the possibilities are intriguing.…”
Section: Anesthesia Teachingmentioning
confidence: 99%
“…In the study published this month in this journal, the authors studied whether implicit learning occurred during anesthesia. 1 The authors enrolled children aged 5-12 yr, and during their anesthetic, from induction through the end of anesthesia, they heard either a sheep sound or white noise. No evidence of learning was found.…”
Section: Anesthesia Teachingmentioning
confidence: 99%
“…Pham et al [7] studied 5-to 12-year-old children who accepted general anesthesia, and found that general anesthesia did not interfere in the process of memory formation. Yin et al [8] compared the effect of propofol and sevoflurane in 7-to 13-year-old children on the short-term and long-term memory, and found that propofol affected the short-term memory, but neither anesthetic affected the long-term memory.…”
Section: Introductionmentioning
confidence: 99%